Syringa josikaea (Oleaceae) biotopes in the Ukrainian Carpathians: Climatic conditions and current dynamics - István HADNAGY; István KOLOZSVÁRI; Mária HÖHN; Erzsébet KOHUT (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
This study aims to identify the key environmental conditions that support the protection and natural regeneration of Syringa josikaea J. Jacq. ex Rchb., a rare Carpathian endemic species listed in the Red Data Book of Ukraine. A detailed analysis of the climatic characteristics of the species’ habitats within the Ukrainian Carpathians is provided. Understanding the climatic factors influencing this local species is crucial for identifying its most vulnerable habitats and developing effective conservation strategies. This approach aligns with international conservation priorities outlined in red lists and other environmental policy documents. The article synthesizes key physical and geographical data, ecological characteristics, and dominant phytocoenological features of 18 documented S. josikaea habitats in Zakarpattia and Lviv Oblasts (regions) (Ukraine). A climatic classification of the species’ habitats was conducted using data from the CarpatClim climate database. Additionally, a Köppen-Geiger climate type map for the Ukrainian part of the species’ distribution range was developed based on climate indicators derived from 338 selected nodes of the regular CarpatClim grid. The results indicate that the species is predominantly found in areas with a temperate continental climate (Dfb). The study presents and discusses the mean statistical values of 21 climate indicators for the period 1961-2010. A comparative analysis of different climatological periods reveals that among the 338 sites examined, only 159 (47% of the total area) have experienced a climatic shift from colder to warmer conditions over the past half-century.